Market Day sebagai Strategi Contextual Learning Math di Pendidikan Anak Usia Dini - Ali, Nabila Nurhaliza; Salamah, Iqna Lailatus; Faozah, Ai Siti (JOECE: Journal of Early Childhood Education, 2025)
Learning mathematics in Early Childhood Education (ECE) plays an important role in building the foundation of logical and systematic thinking from an early age. The introduction of mathematical concepts such as number, value of money, measurement, and counting operations can be done in a fun way through activities that are contextual and close to children's lives, one of which is through market day activities. This study aims to analyze the implementation of market day as a contextual learning math strategy in ECE, with a descriptive qualitative approach. Data were collected through open-ended interviews with teachers, direct observation during the activities, and documentation in the form of photos and field notes. The results showed that market day had a positive impact on improving the understanding of basic math concepts in a contextual way. Children are actively involved in a simple buying and selling process that allows them to learn to count, recognize the value of money, and understand the concepts of more and less and addition in a real way. In addition, this activity also supports children's social-emotional development through interaction, cooperation, and communication. This study found novelty in the integration of numeracy and social skills in one authentic activity that is relevant to the Contextual Teaching and Learning (CTL) approach in early childhood education.